Analisis Sentimen Film Kuliah Kerja Nyata (Kkn) Di Desa Penari Menggunakan Metode Naive Bayes - Salsa Bella Putri; Yonawati Nur Anisa; Nurirwan Saputra (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2022)
The film of Kuliah Kerja Nyata (KKN) in the Dancing Village which is being discussed among the Indonesian people is a film based on a novel by a simpleman entitled "KKN in the Dancing Village". The film tells the story of a group of students who are carrying out their KKN activities in a village in East Java where in that village there are still prohibitions that must not be violated by a group of students which caused the death of two students who were carrying out KKN in that village. Thanks to the broadcast, which is being widely discussed, it has formed positive and negative responses from the community towards this KKN film in Dancer Village. So this study aims to analyze the test results of 550 training data using the Naïve Bayes classification method taken from Instagram posts that have positive comments (105), negative (43), neutral (288), very positive (37) and very negative (36). This sentiment analysis produces an accuracy value of 60.7073%.